Roles of macrophages in lupus nephritis - Cheng, Yaqian; Liu, Lulu; Ye, Yufei; He, Yingxue; Hu, Wenwen; Ke, Haiyan; Guo, Zhi-Yong; Shao, Guojian (Frontiers in Pharmacology, 2024)
As a common and serious complication of systemic lupus erythematosus (SLE), lupus nephritis (LN) is characterized by proteinuria and hematuria and elevated serum creatinine levels. The pathological changes of LN are mainly the deposition of multiple immune complexes inside and outside the glomerulus, causing immune cell infiltration and increased release of proinflammatory cytokines, which lead to varying degrees of glomerular and tubulointerstitial damage. Macrophages can polarize into two different phenotypes, proinflammatory M1 macrophages and anti-inflammatory M2 macrophages that promote repair and fibrosis, and these macrophages affect the onset and progression of LN in multiple ways. In this article, we review the role of macrophages in the development of LN and how macrophages and their products act as disease markers and targets in the diagnosis and treatment of LN.